The Message of Household Harmony in the Song Lyrics of Dikir al-Burdah among the Malay Community in Sarawak: (Mesej Kerukunan Rumah Tangga dalam Seni Kata Lagu Dikir al-Burdah di Sarawak) (Malay Literature, 2018)
This study is based on the practice of the Malay community in Sarawak which makes the performance of dikir al-Burdah as part of the event in the wedding ceremony. In practice, dikir al-Burdah is usually presented in the morning as a starting for a bersanding ceremony, with the intention of applying for the ceremony. Based on its role in the Malay wedding ceremony in Sarawak, this study examined specifically the art of the song dikir al-Burdah related to marriage. This study outlines two objectives, namely identify the messages contained in the art of the word dikir al-Burdah related to marriage, and then evaluate the alignment of the message with the teachings of Islam. This study adopts a text analysis approach, by making five songs of the word dikir al-Burdah derived from the An-Nur Organization, Kampung Melango Baru, Saratok District, Sarawak, as texts. The analysis found that all the songs of the word dikir al-Burdah which were examined addressed the message of household harmony, which were found to be in line with the teachings of Islam as contained in the al-Qur'an and Hadith.Keywords: dikir al-Burdah; An-Nur Organization, Kampung Melango Baru, wedding ceremony, message, Islam